LLSorb: a latest extraordinary Blue wonder / Sarah Laila Mohd Jan … [et al.] - Mohd Jan, Sarah Laila; Megat Hanafiah, Megat Ahmad Kamal; Mat Hussin, Zurhana; Alias, Munirah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Methylene Blue (MB), a cationic dye is difficult to degrade in the environment. Severe exposure to MB will increase the heart rate, vomiting, shock, Heinz body formation, cyanosis, jaundice, quadriplegia and tissue necrosis in humans. The conventional methods used to remove MB are coagulation and flocculation, oxidation or ozonation, membrane separation and activated carbon adsorption, but these methods are very expensive. This research discovered a new effective adsorbent material Leucaena leucocephala (LL) for MB removal. This plant is abundant and can be easily grown in tropical climate. LL has a high capacity to remove MB, which is 200 mg/g. LL can remove 50 ppm MB in just 120 min. LL is much cheaper to produce (<RM 1 /kg) compared to activated carbons (RM 6/kg). In addition, LL is easy to regenerate, which is difficult to achieve by activated carbons. The conversion of this type of plant waste into a low cost dye biosorbent offers a cost effective and eco-friendly alternative to existing technologies for treating colored wastewater Adsorbent